Measuring nutrition-water interactions from space - Amarnath, Giriraj (2020)
Background Water stress poses serious threats to human lives, livelihoods and business stability. As per WRI, more than 61 countries face high to extreme levels of water stress a narrow gap between supply and demand leaves countries vulnerable to fluctuations like droughts or increased water withdrawals, which is why we’re seeing more and more communities facing their own “Day Zeros” and other crises. It is important to understand cascading effects of climate change and how it impacts food security and nutrition among vulnerable smallholder farmers and build resilience.